Legitimising detention and deportation of illegalised migrant families: reconstructing public controversies in Belgium and the Netherlands. - Wittock, Nathan; Cleton, Laura; Vandevoordt, Robin; Verschraegen, Gert (Journal of Ethnic & Migration Studies, 2023)
In Belgium and the Netherlands, the detention and deportation of illegalised migrant families with underage children has recently caused public controversy, resulting in the eruption of anti-deportation protests. This controversy is rooted in the unresolved tension for liberal states to protect children's rights on the one hand, while limiting 'unwanted migration' on the other. Previous literature documents protest reactions to efforts to deport families with underage children, as well as general state tactics to legitimize such coercion. This paper instead centres the state's legitimation work in response to societal protest and draws on publicly available material on two recent controversies: the Belgian debate on family detention and the determination of the child pardon in the Netherlands. For Belgium we highlight that the government frames detention as the 'ultimate measure', used only when less restrictive measures 'failed'. For the Netherlands we show how the government reallocates political responsibility from elected officials to bureaucrats. Both strategies transform what is essentially a moral-political debate into a web of administrative procedures and discussions on legal conditions. The Belgian and Dutch governments thus invisibilize moral conflict by drawing it outside the realm of democratic politics, to the backstage of bureaucratic administration.